2010
DOI: 10.1007/s10450-010-9232-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH of the BSA solutions on velocity of the rising bubbles and stability of the thin liquid films and foams

Abstract: Influence of pH of the BSA solutions on velocity of the rising bubbles, stability of foams, and properties of single foam and wetting films was studied. It was found that the solution pH affected significantly the BSA surface activity and properties of the protein adsorption layer under dynamic and static conditions. At pH close to the isoelectric point (pH IEP = 4.8) the BSA showed the highest surface activity. The equilibrium microscopic foam films of thicknesses of 64-80 nm, depending on the BSA concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…The terminal velocities of the bubbles (u t ) rising in columns of L 9 = 2 and L 11 = 10 mm were 30.5 ± 0.1 cm/s and 34.3 ± 0.1 cm/s, respectively. The u t of the bubble calculated for the larger column remains in very close agreement with the experimentally determined value u t = 34.7 ± 0.2 cm/s . Similar trends can be observed for bubble shape deformation χ, presented in Figure .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The terminal velocities of the bubbles (u t ) rising in columns of L 9 = 2 and L 11 = 10 mm were 30.5 ± 0.1 cm/s and 34.3 ± 0.1 cm/s, respectively. The u t of the bubble calculated for the larger column remains in very close agreement with the experimentally determined value u t = 34.7 ± 0.2 cm/s . Similar trends can be observed for bubble shape deformation χ, presented in Figure .…”
Section: Resultssupporting
confidence: 87%
“…The u t of the bubble calculated for the larger column remains in very close agreement with the experimentally determined value u t ¼ 34.7 AE 0.2 cm/s. [35] Similar trends can be observed for bubble shape deformation x, presented in Figure 8. For the column of L 9 ¼ 2 mm the average value of is 1.43, i.e.…”
Section: Determination Of Bubble Motion Parameterssupporting
confidence: 79%
“…39 It has been reported that protein molecules show the highest surface activity and are generally adsorbed most readily to surfaces when their pH is close to the isoelectric point of the surface. 40 However, most of the FN was lost during rinsing as the high-molecular-weight macromolecule FN barely assembled into the nanotubes. This can explain why the highest concentration of bound protein after the rinsing step was constituted by histone ( Figure 9B).…”
Section: Early Cell Adhesion and Proliferation Abilitymentioning
confidence: 99%
“…These parameters are: film thinning times, critical concentration for black film formation, film stability in terms of probability for stable black foam film formation, film thickness and dependence of its change under applied external pressure, interactions with substances in the bulk, etc. They could be used to direction of optimization and improvement the production technologies as well as development of new generation of therapeutic surfactant preparations [16,17,18,19].…”
Section: Smart Systems and Formulations With Possible Medical Applicamentioning
confidence: 99%